Hadith #4866 - Sunan Abi Dawud - Abdur Rahman bin Ata'a عبد الرحمن بن عطاء; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Jabir ibn 'Abdullah; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
‘Abbad b. Tamim quoted his paternal uncle as saying that he had seen the Messenger of Allah(ﷺ) lying on his back in the mosque according to Qa’nabi’s version) placing one foot over the other.
Grade: Sahih